Experiential Learning: How It can Have Effect on Iranian EFL Learners’ Language Growth and Personal Development - Maryam Azarian (Indonesian EFL Journal: Journal of ELT, Linguistics, and Literature, 2019)
The present study was carried out to determine the effect of experiential learning on a group of Iranian EFL learners' language growth and personal development. A group of male and female sophomore learners of English (N=30) participated in the study. After receiving the treatment in the form of experiential learning in the first session, the participants were given questionnaires, the content of which was about this type of learning. The purpose was to collect their comments about experiential learning and to see which types of experiential activities were more popular among the participants. In the second session, they were randomly divided into two groups who were exposed to different methods of teaching, content-based traditional method and experience-based method. Then they were given a reading test, the result of which indicated which method of teaching was more successful. The quantitative analysis of the data with regard to the questionnaires showed that most of the students showed a positive feeling towards experiential learning. The quantitative analysis of the data also indicated that those who received experience-based method of teaching significantly outperformed the other group.